Laminate film and battery
Patent Information
- Application Number
- JP2022148524
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-16
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2042-09-16
AI Technical Summary
【0012】 本開示によれば、新規なラミネートフィルム、特に高いガスバリア性及び/又は高い耐熱性を有する新規なラミネートフィルムを提供できる。
Smart Images

Figure 0007632425000001 
Figure 0007632425000002 
Figure 0007632425000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate film and a battery. [Background technology]
[0002] In recent years, various techniques for sealing contents, particularly batteries, using laminate films have been disclosed (Patent Documents 1 to 3).
[0003] For example, Patent Document 1 discloses a laminate film for battery exteriors, which is formed by laminating at least a protective layer, a first adhesive layer, a metal foil containing at least aluminum, a second adhesive layer, and a resin sealant layer in this order, wherein a boehmite film having a contact angle with water of 5° or more and 70° or less is formed on the surface of the metal foil that contacts the second adhesive layer, the second adhesive layer contains at least an acid-modified polyolefin resin, and the metal foil and the second adhesive layer are bonded together by a thermal lamination method.
[0004] Moreover, Patent Documents 2 and 3 disclose an all-solid-state battery in which an all-solid-state battery laminate is sealed with a laminate film. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-045737 A [Patent Document 2] JP 2018-133175 A [Patent Document 3] JP 2020-091995 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described in Patent Document 1, laminate films generally provide barrier properties by using a metal foil containing aluminum, and also allow laminate films to be heat-sealed to each other by using a resin sealant layer.
[0007] Such laminate films can provide good barrier properties to the contents sealed therein, and various techniques have been disclosed for sealing contents that are highly sensitive to moisture, such as battery stacks, food, medicines, and electronic components, particularly battery stacks (Patent Documents 1 to 3).
[0008] However, the properties required for laminate films vary depending on the application, and therefore new laminate films having properties different from those of conventional laminate films are required. Also, laminate films for contents that are particularly sensitive to moisture, such as battery stacks, require even higher gas barrier properties. Also, depending on the application, it may be preferable for the laminate film to have high heat resistance.
[0009] In response to this, the present disclosure provides a novel laminate film, in particular a novel laminate film having high gas barrier properties and / or high heat resistance. [Means for solving the problem]
[0010] As a result of intensive research, the present inventors have found that the above problems can be solved by the following means, and have completed the present invention. That is, the present invention is as follows:
[0011] <Aspect 1> A laminate film having a metal foil and a sealant-forming layer laminated to the metal foil, the sealant-forming layer comprises glass frit and a binder resin bonding the glass frits together; and The 5% weight loss temperature of the binder resin is lower than the glass transition point of the glass constituting the glass frit. Laminating film. <Aspect 2> 2. The laminate film according to claim 1, wherein the glass frit has a glass transition point of 250° C. or higher and 500° C. or lower. <Aspect 3> 3. The laminate film of claim 1 or 2, comprising, in this order, a vitreous protective layer, the metal foil, and the sealant-forming layer. <Aspect 4> 1. A battery having a solid-state battery stack and a laminate film at least partially encapsulating the solid-state battery stack, the laminate film comprising a metal foil layer and a glass sealant layer laminated to the metal foil. <Aspect 5> 5. The solid-state battery of embodiment 4, wherein the solid-state battery stack is a sulfide solid-state battery stack. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a novel laminate film, in particular a novel laminate film having high gas barrier properties and / or high heat resistance. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view showing two examples of the laminate film of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing a state in which laminate films of the present disclosure are bonded to each other (FIG. 2(a)), and a state in which a laminate film of the present disclosure is bonded to a substrate (FIG. 2(b)). [Diagram 3] FIG. 3 is a cross-sectional view showing a state in which a solid-state battery stack is sealed with the laminate film of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. However, the embodiments shown in the drawings are merely examples of the present disclosure and are not intended to limit the present disclosure.
[0015] Lamination film The laminate film of the present disclosure includes a metal foil and a sealant-forming layer laminated on the metal foil. The sealant-forming layer includes a glass frit and a binder resin that bonds the glass frit to each other. The 5% weight loss temperature of the binder resin is lower than the glass transition temperature of the glass constituting the glass frit.
[0016] According to the laminate film of the present disclosure, in one embodiment, when laminate films of the present disclosure are laminated together with their sealant-forming layers in contact with each other, and then heated and optionally pressed, the binder resin of the sealant-forming layer is at least partially removed by thermal decomposition, and the glass frit of the sealant-forming layer is softened, thereby bonding the glass sealant layers formed from the sealant-forming layers to each other.
[0017] Furthermore, according to the laminate film of the present disclosure, in another embodiment, when the laminate film of the present disclosure is laminated to another substrate such that the sealant-forming layer is in contact with the other substrate, and then heated and optionally pressed, the binder resin of the sealant-forming layer is at least partially removed by thermal decomposition, and the glass frit of the sealant-forming layer is softened, thereby bonding the glass sealant layer formed from the sealant-forming layer to the substrate.
[0018] That is, the laminate film of the present disclosure can be used in the same manner as conventional laminate films that use a resin sealant layer made of a thermoplastic resin, except that the heating temperature used is a temperature that exceeds the glass transition point of the glass that constitutes the glass frit.
[0019] Conventional laminate films have a metal foil and a resin sealant layer laminated on the metal foil, and the resin sealant layer is made of a thermoplastic resin such as polyethylene. Therefore, in the conventional laminate film, the metal foil can provide high barrier properties in the direction perpendicular to the surface direction of the laminate film, but in the surface direction of the laminate film, the barrier properties against the diffusion of gas passing through the thermoplastic resin from the end of the laminate film in the surface direction may be insufficient. In addition, conventional laminate films have a problem in that their heat resistance temperature is limited by the thermoplastic resin used in the resin sealant layer.
[0020] In contrast, according to the laminate film of the present disclosure, the layer obtained by heating and optionally pressing the sealant-forming layer is a glass sealant layer, and therefore high gas barrier properties and / or high heat resistance can be provided.
[0021] The laminate film of the present disclosure may optionally have a vitreous protective layer. In this case, the laminate film of the present disclosure may have a vitreous protective layer, the above-mentioned metal foil, and the above-mentioned sealant-forming layer in this order. In this case, the glass constituting the vitreous protective layer may be the same as or different from the glass constituting the glass frit. The vitreous protective layer may also be formed by forming the above-mentioned sealant-forming layer on a metal foil, and then heating and optionally pressing the metal foil to remove the binder resin of the sealant-forming layer by pyrolysis, and softening the glass frit of the sealant-forming layer to form a glass layer.
[0022] Specifically, the laminate film of the present disclosure can have a configuration as shown in FIG.
[0023] A laminate film 100 according to the present disclosure shown in Fig. 1(a) has a metal foil 10 and a sealant-forming layer 20 laminated on the metal foil 10. The sealant-forming layer 20 also contains a glass frit 23 and a binder resin 24 that bonds the glass frit 23 to each other. A laminate film 200 according to the present disclosure shown in Fig. 1(b) further has a vitreous protective layer 30, and has the vitreous protective layer 30, the metal foil 10, and the sealant-forming layer 20 in this order.
[0024] When the laminate films of the present disclosure are laminated together so that the sealant-forming layers are in contact with each other, and then heated and optionally pressed, at the end of the portion where the glass sealant layers are bonded together, as shown in Fig. 2(a), the first metal foil 10a, the first glass sealant layer 20a derived from the first sealant-forming layer, the second glass sealant layer 20b derived from the second sealant-forming layer, and the second metal foil 10b are laminated in this order, and the glass sealant layer 20a and the second glass sealant layer 20b are bonded to each other. Here, the first metal foil 10a and the first glass sealant layer 20a are the portion 100a derived from the first laminate film of the present disclosure, and the second metal foil 10b and the second glass sealant layer 20b are the portion 100b derived from the second laminate film of the present disclosure.
[0025] Furthermore, when the laminate film of the present disclosure is laminated on another substrate with the sealant-forming layer in contact with the other substrate, and then heated and optionally pressed, as shown in Fig. 2(b), the metal foil 10c, the glass sealant layer 20c derived from the sealant-forming layer, and the substrate 500 are laminated in this order, and the glass sealant layer 20c is bonded to the substrate 500. Here, the metal foil 10c and the glass sealant layer 20c are the portion 100c derived from the laminate film of the present disclosure.
[0026] (Metal foil) The metal foil used in the laminate film of the present disclosure may be any metal foil capable of forming a laminate film. This metal foil must be able to withstand the heat and optional pressure required to form a glass sealant layer from the sealant-forming layer by heating and optional pressing, and is therefore preferably an aluminum foil, a copper foil, or a stainless steel foil, particularly a stainless steel foil. In addition, the metal foil may be any metal foil used in a sealant film having a conventional resin sealant layer. The metal foil used in the laminate film of the present disclosure may be subjected to any surface treatment, such as surface roughening or surface sloping, in order to improve bonding with the sealant-forming layer or the glass sealant layer obtained from the sealant-forming layer.
[0027] (Sealant forming layer) The sealant-forming layer used in the laminate film of the present disclosure includes a glass frit and a binder resin that bonds the glass frit to each other. Here, the 5% weight loss temperature of the binder resin is lower than the glass transition point of the glass constituting the glass frit. According to this, when obtaining a glass sealant layer from the sealant-forming layer by heating and optionally pressing, the binder resin can be at least partially removed, thereby facilitating the formation of the glass sealant layer from the sealant-forming layer.
[0028] For example, the 5% weight loss temperature of the binder resin may be lower than the glass transition point of the glass (inorganic glass) constituting the glass frit by 5° C. or more, 10° C. or more, or 20° C. or more.
[0029] The ratio of the glass frit to the binder resin may be 0.1 mass% or more, 0.5 mass% or more, 1 mass% or more, 2 mass% or more, 3 mass% or more, 4 mass% or more, or 5 mass% or more of the binder resin relative to the total of the glass frit and the binder resin, and may be 20 mass% or less, 15 mass% or less, 10 mass% or less, 8 mass% or less, 6 mass% or less, or 5 mass% or less. This ratio is preferably as small as possible within a range that allows bonding between glass film lits, so as not to hinder the formation of a glass sealant layer from the sealant forming layer.
[0030] Here, the "5% weight loss temperature" of the binder resin can be determined by heating the binder resin at a temperature range of 30°C to 480°C at a heating rate of 10°C / min using a thermogravimetric and differential thermal analyzer or the like.
[0031] As the binder resin usable in the laminate film of the present disclosure, any binder resin can be used that can fix the glass frit on the metal foil to form a sealant-forming layer and has a 5% weight loss temperature lower than the glass transition point of the glass constituting the glass frit. As such a binder resin, any binder resin such as an acrylic binder, a urethane binder, a rubber binder (e.g., styrene butadiene rubber), or a combination thereof can be used. Note that, when the binder resin is a combination of multiple resins, the 5% weight loss temperature can be considered to be the 5% weight loss temperature of the entire binder resin.
[0032] The "glass transition point" of the glass constituting the glass frit can be evaluated by differential thermal analysis (DTA) measurement in accordance with JIS K 0129: 2005. Specifically, for example, in a differential curve of a DTA curve obtained using α-alumina as a reference, the temperature of the center of the first endothermic peak (the intersection of the tangents at the first inflection point and the second inflection point) can be determined as the glass transition point (Tg).
[0033] The glass transition point of the glass constituting the glass frit may be 250° C. or more and 500° C. or less. Here, the glass transition point may be 250° C. or more, 270° C. or more, 280° C. or more, 290° C. or more, 300° C. or more, 310° C. or more, 320° C. or more, 330° C. or more, 340° C. or more, or 350° C. or more, and may be 500° C. or less, 450° C. or less, 400° C. or less, 350° C. or less, 340° C. or less, 330° C. or less, 320° C. or less, 310° C. or less, 300° C. or less, 290° C. or less, 280° C. or less, or 270° C. or less.
[0034] In the laminate film of the present disclosure, when the glass transition temperature of the glass constituting the glass frit is relatively low, for example, 350° C. or lower, the laminate film of the present disclosure can be used to unexpectedly seal a solid battery stack using a sulfide-based solid electrolyte that has been considered to have relatively low heat resistance, to form a sulfide-based solid battery.
[0035] In this regard, the present disclosure et al. have confirmed that, as a result of heat treating a positive electrode active material layer including a nickel-cobalt-manganese positive electrode active material coated with lithium niobate and a Li2S-P2S5-based solid electrolyte, the ionic conductivity of the solid electrolyte decreases when the temperature exceeds about 300°C, but the ionic conductivity is maintained at 360°C or lower.
[0036] Examples of glasses having such a relatively low glass transition point include silicate-based glasses, borate-based glasses, bismuth silicate-based glasses, borosilicate-based glasses, vanadium oxide-based glasses, and phosphate-based glasses.
[0037] Examples of silicate glasses include those mainly composed of SiO2-ZnO, SiO2-Li2O, SiO2-Na2O, SiO2-CaO, SiO2-MgO, SiO2-Al2O3, etc. Examples of bismuth silicate glasses include those mainly composed of SiO2-Bi2O3-ZnO, SiO2-Bi2O3-Li2O, SiO2-Bi2O3-Na2O, SiO2-Bi2O3-CaO, etc. Examples of borate glasses include those mainly composed of B2O3-ZnO, B2O3-Li2O, B2O3-Na2O, B2O3-CaO, B2O3-MgO, B2O3-Al2O3, etc. Borosilicate glasses include those mainly composed of, for example, SiO2-B2O3-ZnO, SiO2-B2O3-Li2O, SiO2-B2O3-Na2O, SiO2-B2O3-CaO, etc. Vanadium oxide glasses include those mainly composed of, for example, V2O5-B2O3, V2O5-B2O3-SiO2, V2O5-P2O5, V2O5-B2O3-P2O5, etc. Phosphate glasses include those mainly composed of, for example, P2O5-Li2O, P2O5-Na2O, P2O5-CaO, P2O5-MgO, P2O5-Al2O3, etc.
[0038] In addition to the above-mentioned main components, these low glass transition point glasses may appropriately contain one or more of SiO2, ZnO, Na2O, B2O3, Li2O, SnO, BaO, CaO, Al2O3, etc. Here, "main component" means that the above-mentioned component accounts for more than 50 mass%, 60 mass% or more, 70 mass% or more, 80 mass% or more, or 90 mass% or more of the weight of the inorganic glass.
[0039] "battery" The battery of the present disclosure has a solid-state battery stack and a laminate film at least partially sealing the solid-state battery stack, the laminate film having a metal foil layer and a glass sealant layer laminated to the metal foil. Such a battery of the present disclosure can be obtained by at least partially sealing the solid-state battery stack constituting the power generating element with the laminate film of the present disclosure. Therefore, in such a battery of the present disclosure, the solid-state battery stack may be sealed only with the laminate film of the present disclosure, or may be sealed with a combination of the laminate film of the present disclosure and another film or substrate.
[0040] Specifically, the battery of the present disclosure can have a configuration as shown in FIG.
[0041] A solid-state battery 1000 according to the present disclosure shown in Fig. 3(a) is a battery having a solid-state battery stack 800 and laminate films 100a and 100b sealing the solid-state battery stack 800, and the laminate films 100a and 100b have metal foil layers 10a and 10b and glass sealant layers 20a and 20b laminated to the metal foil. Another solid-state battery 2000 according to the present disclosure shown in Fig. 3(b) is a battery having a combination of a solid-state battery stack 800 and a laminate film 100c sealing the solid-state battery stack 800 and a substrate 500, and the laminate film 100c has a metal foil layer 10c and a glass sealant layer 20c laminated to the metal foil.
[0042] In the present disclosure, examples of the solid-state battery stack include a solid-state lithium-ion battery stack, a solid-state sodium-ion battery stack, a solid-state magnesium-ion battery stack, and a solid-state calcium-ion battery stack, etc. Among these, the solid-state battery stack is preferably a solid-state lithium-ion battery stack or a solid-state sodium-ion battery stack, and more preferably a solid-state lithium-ion battery stack.
[0043] The solid-state battery of the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because secondary batteries can be repeatedly charged and discharged, and are useful, for example, as in-vehicle batteries. Therefore, the solid-state battery of the present disclosure is preferably a solid-state lithium-ion secondary battery.
[0044] In addition, the solid-state battery of the present disclosure may preferably be a sulfide solid-state battery, i.e., a battery having a solid-state battery stack having a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, at least one of which contains a sulfide solid electrolyte.
[0045] Depending on the application of the battery, it may be preferable to mount the battery on a printed circuit board using a soldering process, particularly a reflow soldering process.
[0046] However, in conventional laminate batteries (pouch batteries) in which the exterior is formed from a conventional sealant film using a resin sealant layer, the resin sealant is weak against heat, and it is considered that these batteries are not suitable for mounting on a printed circuit board using a soldering process.
[0047] In contrast, in the battery of the present disclosure, the sealant layer is a glass sealant layer, which allows the battery to be mounted to a printed circuit board using a soldering process, particularly a reflow soldering process.
[0048] In the context of this disclosure, the term "reflow soldering process" refers to a process in which solder that has been applied in advance at room temperature is later heated to melt and perform soldering.
[0049] In the "reflow soldering process", a paste or cream-like solder is applied or printed on the required locations of a printed circuit board, then the object to be soldered is placed in a predetermined position on the printed circuit board, and finally the printed circuit board is passed through a high-temperature reflow furnace to melt the solder and solder the object to be soldered and the printed circuit board. Here, examples of heating methods in the reflow furnace include an infrared method and a hot air method.
[0050] In contrast to the above-mentioned "reflow soldering process," a process in which soldering is performed by allowing heat-melted solder to flow between an object to be soldered and a printed circuit board is sometimes referred to as a "flow soldering process." EXAMPLES
[0051] Example 1 (Method of making laminate film) A low glass transition point glass (57V2O5-23TeO2-20P2O5 (mol %), glass transition point: 276°C) frit and a binder resin (acrylic resin, 5% weight loss temperature: approximately 250°C) were mixed at a ratio of 95:5 (mass ratio) and applied to a stainless steel foil using a doctor blade with a coating gap of 100 μm to form a laminate film of Example 1. Here, the laminate film of this Example had a sealant-forming layer on the stainless steel foil, which contained glass frit and a binder resin that bonded the glass frits to each other.
[0052] The prepared laminate film was pressed in a uniaxial press under the following conditions: Press pressure: 10kN Press temperature: 276℃ Press time: 5 minutes
[0053] It was confirmed that the binder resin was partially decomposed and reduced, and the glass frit was sintered to form a glass sealant layer on the stainless steel foil. In addition, although residual binder components were scattered within the glass sealant layer, they did not interfere with the integrity of the glass sealant layer.
[0054] Example 2 Two sheets of the sealant film obtained in Example 1 were prepared, superimposed on each other so that the sealant-forming layers were in contact with each other, and pressed under the same conditions as in Example 1.
[0055] It was confirmed that the binder resin was partially decomposed and reduced, the glass frit was sintered to form a glass sealant layer on the stainless steel foil, and the glass sealant layers derived from the sealant-forming layers that were superposed so as to be in contact with each other were bonded to each other. In addition, although residual binder components were scattered within the glass sealant layer, they did not interfere with the integrity of the glass sealant layer.
[0056] Comparative Example 1 A laminate film of Comparative Example 1 was formed in the same manner as in Example 1, except that styrene-butadiene rubber (5% weight loss temperature: approximately 350°C) was used as the binder resin instead of acrylic resin (5% weight loss temperature: approximately 250°C), and pressed with a uniaxial press.
[0057] According to this, the binder resin was not substantially reduced due to thermal decomposition, and the sintering of the glass frit was insufficient. [Explanation of symbols]
[0058] 100, 100a, 100b, 100c, 200, Laminate film 10, 10a, 10b, 10c metal foil 20 Sealant Cambium 20a, 20b, 20c Glass sealant layer 23 Glass frit 24 Binder Resin 30 Vitreous protective layer 500 Base material 1000, 2000 solid state battery 800 Solid-state battery stack
Claims
1. A laminate film having a metal foil and a sealant-forming layer laminated to the metal foil, the sealant-forming layer comprises glass frit and a binder resin bonding the glass frits together; and The 5% weight loss temperature of the binder resin is lower than the glass transition point of the glass constituting the glass frit. Laminating film.
2. 2. The laminate film according to claim 1, wherein the glass constituting the glass frit has a glass transition point of 250° C. or higher and 500° C. or lower.
3. 2. The laminate film of claim 1, comprising, in order, a vitreous protective layer, said metal foil, and said sealant-forming layer.
4. 1. A method for manufacturing a solid-state battery having a solid-state battery stack and a laminate film at least partially encapsulating the solid-state battery stack, comprising: The laminate film has a metal foil and a glass sealant layer laminated to the metal foil; and A method for producing a solid-state battery, comprising the steps of: (i) laminating the laminate films according to any one of claims 1 to 3 so that the sealant-forming layers are in contact with each other, and then heating the laminate films to at least partially remove the binder resin of the sealant-forming layer by thermal decomposition and soften the glass frit of the sealant-forming layer, thereby bonding the glass sealant layers formed from the sealant-forming layers to each other; or (ii) The laminate film according to any one of claims 1 to 3 is laminated onto another substrate such that the sealant-forming layer is in contact with the other substrate, and then heated to at least partially remove the binder resin of the sealant-forming layer by thermal decomposition, and to soften the glass frit of the sealant-forming layer, thereby bonding the glass sealant layer formed from the sealant-forming layer to the substrate.
5. 5. The method of claim 4, wherein the solid state battery stack is a sulfide solid state battery stack.
Citation Information
Patent Citations
Soft package battery shell, soft package battery and battery module
CN212485420U
Slippery resin composition
JP1999246705A
Extrusion-laminated film
JP2002225197A
Thin-film battery sealed package
JP2010519675A
Electronic component and its manufacturing method, and sealing material paste used therefor
JP2014024730A